International Conference Enhanced Genepool Utilization - Capturing wild relative and landrace diversity for crop improvement, Cambridge, United Kingdom, 16-20 June 2014. Book of Abstracts - Dias, S.; Dulloo, Mohammad Ehsan; Maxted, Nigel; Kell, S.; Thörn, E.; Smith, L.; Preston, J.; Hutchinson, S. (Bioversity International, 2014)
This conference presents the culmination of the PGR Secure project (www.pgrsecure.org) – a collaborative project involving eleven partners funded under the EU Seventh Framework Programme, THEME KBBE.2010.1.1-03, 'Characterization of biodiversity resources for wild crop relatives to improve crops by breeding', Grant agreement no. 266394. It is jointly organized with the section on genetic resources of the European Association for Research on Plant Breeding (EUCARPIA). This international conference showcases innovative and potential novel characterization techniques and conservation strategies to identify and safeguard crop wild relative (CWR) and landrace (LR) genetic diversity to increase potential options for crop improvement as a means of underpinning food security in the face of climate change. The conference brings together a wide range of biodiversity expertise from the international community to debate current and future enhanced conservation and utilization of CWR and LR diversity for improving agricultural production, increasing food security and sustaining the environment for better livelihoods. The conference represents a landmark in the plant genetic resources science arena, highlighting exotic plant germplasm as a potentially critical but neglected resource for crop improvement. Part 1 of the book of abstracts contains the abstracts of the oral presentations and Part 2, those of the posters. They are organized under the four conference themes, viz. characterization techniques, conservation strategies, facilitating CWR and LR use and informatics development. The oral presentations will be the subject of a book entitled “Enhancing Crop Genepool Use: Capturing wild relative and landrace diversity for crop improvement” that will be published by CABI as the conference proceedings. All duly registered participants will be receiving a copy of the book when it is published.